The impact of atherosclerotic risk factors on disease progression in patients with previously diagnosed nonobstructive coronary artery disease: factors affecting coronary artery disease progression. Issue 4 (June 2020) - Durmaz, Eser; Ikitimur, Baris; Karadag, Bilgehan; Barman, Hasan Ali; Atici, Adem; Koca, Damla; Raimoglu, Utku; Karaca, Orhan Furkan; Mutlu, Deniz; Ongen, Zeki
Abstract : Objective: Since coronary artery disease (CAD) is a slow progressive disease, management and appropriate follow-up of patients with nonobstructive coronary artery disease (NOCAD) remains challenging, and there are no clear guidelines recommending a follow-up strategy and indications for repeat invasive coronary angiography (ICA). We investigated the predictors of the development of obstructive CAD in patients with previously diagnosed NOCAD. Methods: We prospectively included 186 patients who previously received a diagnosis of NOCAD with invasive coronary angiogram and underwent repeat ICA. Patients' demographics, clinical characteristics, biochemical analyses were recorded. Obstructive CAD is defined as >50% luminal narrowing in any epicardial coronary artery with a diameter of >2 mm. Results: A total of 186 patients (105 male) were assigned into our study. Mean age was 64.77 ± 10.31 in patients with obstructive CAD (n = 60) vs. 61.87 ± 9.94 in NOCAD patients (n = 126) ( P value: 0.068). The median time interval between index and follow-up coronary angiograms was 8 (5–10) years. There was no significant difference between groups with respect to LDL and Hs-CRP levels ( P value: 461 and 354, respectively). Although patients with obstructive CAD have more comorbidities, multivariate analyses revealed that there was no significant difference between groups. On the contrary, the total number of risk factors were significantly associated with the development of obstructive CAD during follow-up. Receiver operating characteristic analyses revealed with a cut-off value of 3.5 risk factors, the sensitivity of 71%, the specificity of 61% and the area under the curve was 0.71 for prediction of obstructive CAD. Conclusion: Our results indicate that no single risk factor alone is related with development of obstructive CAD; however, patients with high number of multiple risk factors are more prone to develop obstructive disease and require closer follow-up.